2016
DOI: 10.1016/j.jinorgbio.2016.02.035
|View full text |Cite
|
Sign up to set email alerts
|

On the ability of CuAβ1-x peptides to form ternary complexes: Neurotransmitter glutamate is a competitor while not a ternary partner

Abstract: In the light of conflicting reports on the ability of copper(II) complexes of amyloid beta (Aβ) peptides to form ternary complexes with small molecules co-present in the biological milieu, we performed a study of coordination equilibria in the system containing Cu(II) ions, the Aβ1-16 peptide, glutamic acid and 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (2-[4-(2-hydroxyethyl)piperazin-1-yl]ethanesulfonic acid, HEPES) buffer. Using potentiometry, isothermal titration calorimetry (ITC), UV-visible spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Instead, we found that these two ligands only competed for Cu(II) at the physiological range of its concentrations. 122 These studies confirmed a pleiotropic and hardly predictable character of Cu(II) interactions with Aβ 1−x peptides.…”
Section: Inorganic Chemistrymentioning
confidence: 83%
See 2 more Smart Citations
“…Instead, we found that these two ligands only competed for Cu(II) at the physiological range of its concentrations. 122 These studies confirmed a pleiotropic and hardly predictable character of Cu(II) interactions with Aβ 1−x peptides.…”
Section: Inorganic Chemistrymentioning
confidence: 83%
“…We checked whether glutamate, which may be co-present with Aβ peptides in glutamatergic synapses, might be a ternary partner for Aβ 1–16 in Cu­(II) binding. Instead, we found that these two ligands only competed for Cu­(II) at the physiological range of its concentrations . These studies confirmed a pleiotropic and hardly predictable character of Cu­(II) interactions with Aβ 1– x peptides.…”
Section: Copper Complexes Of Aβ1–x Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent dissociation constant of Aβ 1−x (x ≥ 16) at pH 7 is ~0.1 nM (Alies et al, 2013; Young et al, 2014) and thus better described as “moderate,” since other metal-binding species with comparable (or higher) capacity to bind Cu 2+ are also present in the central nervous system (CNS). For example, glutamate also reaches transiently high local concentration during synaptic signaling (Danbolt, 2001), making it competitive at relevant physiological concentrations (Frączyk et al, 2016), while other neurotransmitters such as histamine (HA) have even higher Cu 2+ affinity than glutamate (Dawson et al, 1990). Aside from one study concluding Aβ 1−42 oligomers have an enhanced affinity ( K d < 3 pM in HEPES pH 7.4; Jiang et al, 2013) that enables them to compete with human serum albumin (HSA), the latter has also been proposed as a major competitor with Aβ for copper ions within the CNS (Rózga and Bal, 2010), effectively competing for 99.9% of Cu 2+ (Perrone et al, 2010) and binding Cu + stronger than Aβ (Lu et al, 2015).…”
Section: Is Biological Aβ Metal Binding Feasible?mentioning
confidence: 99%